Une célébration du roi ? Pierre Patte et ses Monumens érigés en France à la gloire de Louis XV - Yvonne Rickert (Les Cahiers de Framespa)
The following text gives an analysis of the book by Pierre Patte, Monumens érigés en France à la gloire de Louis XV, published in 1765, two years after the inauguration of the Parisian royal statue of Louis XV. Patte treats different projects for the mentioned royal square. The article aims to show how 18th century architect Pierre Patte managed, through a praise of the king of France, to criticise Louis XV in an oblique way.